PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK-PAIR-SHARE TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR PESERTA DIDIK PADA KONSEP KINGDOM PLANTAE DI SMA NEGERI 5 BANDA ACEH - Hasanuddin Hasanuddin; Iswadi Iswadi; Ismul Huda; Marlina Marlina (Jurnal Dedikasi Pendidikan, 2022)
This study aims to improve the quality of biology learning process through think- Pair-Share (TPS) models, to improve student learning Outcomes, to describe teachers and student learning activities, and to determine the learning completeness level. The population of this study was 324 students of grade X. The sample was 20 students for the experiment class from class I5 and 20 students for the control class. The sample selected was based on a lottery system. The instrument in this study was a test. The data gathered was analyzed with a t-test. The result showed that the implementation of TPS on the Plantae concept can improve student learning outcomes. The learning process activities were well concluded. The dominant activity of teachers was as a facilitator while the dominant activity of students was doing on student worksheets in pairs. At the classical level as learning competency, The experiment class reached 80 % and the control class reached 60 % of a 100.